Team development through leader mindfulness and authentic leadership: Leader mindfulness as an antecedent to authentic leadership and its relationship with team development as seen in actual turnover, turnover intention, performance, internal mobility, and promotions - WERMELINGER, Stefan Juerg (Institutional Knowledge at Singapore Management University, 2024)
The following research examines leader mindfulness as an antecedent to authentic leadership and its relationship with team development seen in actual turnover, turnover intention, performance, internal mobility, and promotions. The study has a significant advantage as team leaders and team members could be surveyed in a real company, and data from the human resource department could be linked to reconstruct the team settings. In addition, insights into internal mobility, actual turnover, and promotions could be calculated. The study uses a theoretical framework that builds on leader mindfulness as an antecedent of authentic leadership and authentic leadership as a root concept for positive leadership and associated benefits. Turnover intention and actual turnover with its associated costs have been identified as challenges within companies. Also, other team development aspects like performance, internal mobility, and promotions need to be better understood in the context of leadership. This research sheds light on these topics as it focuses on leader mindfulness as an antecedent of authentic leadership and its effect on team development. The link between leader mindfulness and authentic leadership was explored as the first step. The results suggest that the awareness dimension of leader mindfulness is positively linked to self-rated authentic leadership and negatively linked to perceived authentic leadership. The study defined a mediation model with leader mindfulness as the independent variable and authentic leadership as the mediator to investigate the impact on the team development variables. No moderated mediation could be found. Consistent results suggested that authentic leadership reduces turnover intention within the teams. The results also showed that authentic leadership can expand managerial capacity, as leaders can have a lower turnover intention even in larger teams. In another model, employee mindfulness was defined as a mediator and span of control, and an a variable indicating if the employee was hired by the current team leader as a moderator. Results showed a positive relationship between employee mindfulness awareness and leader mindfulness awareness. Also, this model suggested that authentic leadership is related to a lower turnover intention. Additional analyses were done focusing on leader compassion. Perceived compassion is related to perceived and self-rated authentic leadership and a lower turnover intention. As the study had self-rated and perceived measurements available, it also showed how well leaders can assess their authentic leadership, compassion, and Leader-Member Exchange (LMX). Data showed good self-awareness for authentic leadership but more considerable differences between self-rated and perceived scales for LMX and compassion.